A systematic review of leadership styles in organizations: Introducing the concept of a task-relationship-change leadership network - Dehghanan, Hamed (2021)
Despite the leadership literature involving a spread spectrum of relevant frameworks to explain leadership behaviors, there is still an ever-increasing demand for more conceptual transparency in leadership styles, characteristics, and their impacts on members and organizations. This study aims to systematically review and identify all the leadership styles and presents a leadership network of all styles based on the seven steps proposed by Scaringella and Radziwon [2018]. A total of 59 articles were consequently selected according to the protocols and then the predominant leadership styles, as well as their characteristics, were investigated and classified in terms of the three criteria namely “task”, “relationship”, and “change” and a 9 × 9 leadership network was created covering retrogressive and passive leadership (frame 1.1), authentic and exchange-oriented leadership (frame 9.1), influential and transactional leadership (frame 1.9), transformational leadership (frame 9.9), and balanced leadership (frame 5.5). The proposed network indeed coherently covers all the leadership styles reviewed and presents a framework for shifting towards transformational leadership. This network should be viewed as a coherent entirety and all the six leadership concepts including training, behaviors, culture, competencies, succession, and evaluation need to be taken into consideration.